The Approach of Jabatan Agama Islam Selangor (JAIS) to Christian evangelism : the case study on Damansara Utama Methodist Church (DUMC) - Muhammad Amier Rostam (AbdulHamid AbuSulayman Kulliyyah of Islamic Revealed Knowledge and Human Sciences,International Islamic University Malaysia, 2022)
This research sought to identify the approaches used by Jabatan Agama Islam Selangor (JAIS), a state-level constituent authority in handling the issue of Christian evangelism activities in Selangor. The research focused on the historical event that occurred in 2011 whereby JAIS had raided the Damansara Utama Methodist Church (DUMC) premise, one of the prominent churches in Petaling Jaya, Selangor. The raid occurred during a Thanksgiving dinner organised by a local non-government Organisation (NGO) called Harapan Komuniti; the NGO was led by a controversial Christian evangelist named Pastor Raymond Koh. The raid incident had caught the attention of various parties such as religious leaders, local news operators, NGOs, the court of law, the state authority, and even the royals. The disturbance had caused serious tension between the local Muslim and Christian communities since such events can be considered part of Christian evangelism, which is against the federal and state laws. This research elaborated on the function and role of JAIS as a religious state body as well as its methodologies in handling Christian evangelism. The importance of having federal and state laws in relation to the freedom of religion was also highlighted. The reality of the raid incident was portrayed based on information and experience gathered from various primary and secondary sources including books, magazines, articles, news, videos gathered from the library, the world wide web, and religious departments. Personal interviews were also carried out with officers from JAIS and a representative from DUMC. This study also highlighted the responses from Muslim leaders, Christian leaders, and NGOs regarding the JAIS raid incident. The findings of the study have proven that Christian evangelism in Selangor is a serious task for JAIS to handle and that JAIS’ approaches have been considered valid. Besides, much less has been written on JAIS’ approaches in handling Christian evangelism especially in relation to the DUMC incident. This research, therefore, has filled this gap.